Security from above and below: A critical ethnography of the health response to violence against women in Timor-Leste. (September 2020) - Wild, Kayli; Gomes, Lidia; Fernandes, Angelina; de Araujo, Guilhermina; McDonald, Susan; Taft, Angela
Abstract: International advocacy and evidence have been critical for shifting the pervasive issue of violence against women onto the health agenda. Guidelines and training packages, however, can be underpinned by Western principles of responding to individual survivors of violence and availability of specialist referral services, which may not be available in many countries. As Timor-Leste and other nations begin to build their health system response to violence against women, it is important to understand the current practices of health providers and the broader sociocultural context of providing care to survivors of violence. During 11 months in the field (February–December 2016), we conducted qualitative interviews with 48 midwives and community leaders in three municipalities in Timor-Leste. The findings reveal that midwives engage at both the individual and collective levels, providing medical care, advice and moral support to survivors of violence as well as gathering support for women within families and communities. Midwives therefore navigate both formal and informal spaces as they respond to domestic and sexual violence. In doing so, they are influenced by their own experiences as women, as health providers imbued with authoritative knowledge, and as part of the wider sociocultural system. We argue that while much progress has been made in frameworks for health systems responding to survivors of violence, more work needs to be done to understand how to support health providers in low- and middle-income countries as they engage with perpetrators, families and communities. There is a need for further discussion of how health systems can address the issue of domestic and sexual violence as a collective social problem, while foregrounding the needs and rights of those experiencing violence. This research has implications for the content of guidelines and training, and importantly, for developing mechanisms to deal with complex social issues within local health services. Highlights: Midwives' responses are diverse, they reinforce or challenge existing inequalities. Midwives engaging with women, men and families need support to do this safely. Laws and formal services are essential, but many midwives do not know about them. Participants said community engagement is key to social change on domestic violence.